2020
DOI: 10.1186/s12888-020-02507-1
|View full text |Cite
|
Sign up to set email alerts
|

How addicted are newly admitted undergraduate medical students to smartphones?: a cross-sectional study from Chitwan medical college, Nepal

Abstract: Background: Increasing smartphone use among adolescents in todays' world has made this handy device an indispensable electronic tool, however, it comes at a price of problematic overuse or addiction. We aim to investigate the prevalence of smartphone addiction among undergraduate medical students and explore its association with various demographic and personal factors. Methods: A pool of 250 undergraduate students completed a survey composed of socio-demographics information, smartphone-use related variables … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
25
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 29 publications
5
25
2
1
Order By: Relevance
“…Smartphone addiction was associated with poorer sleep. Our estimated prevalence is consistent with other reported studies in young adult populations globally, which are in the range of 30-45%, and with Yang et al (29) who studied a similar university population in the UK (4,(36)(37)(38)(39). Noe et al (40).…”
Section: Discussionsupporting
confidence: 92%
“…Smartphone addiction was associated with poorer sleep. Our estimated prevalence is consistent with other reported studies in young adult populations globally, which are in the range of 30-45%, and with Yang et al (29) who studied a similar university population in the UK (4,(36)(37)(38)(39). Noe et al (40).…”
Section: Discussionsupporting
confidence: 92%
“…Findings similar to our study have also been reported by Hassan and Hassan[ 30 ] and Karki et al . [ 31 ] in other South-east Asian countries. The variance in the above findings may be attributed to the disparity in the participants' psycho-social and cultural environments based on different parts of the world.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Hawi and Samaha (2016) determined that, regardless of the students' genders, those who were at low risk of smartphone addiction, as determined by the SAS, had a higher chance of achieving higher academic performance than those at high risk of smartphone addiction (Hawi & Samaha, 2016). In a study performed by Karki, Singh, Paudel et al (2020), they determined that males are more addicted to smartphones than the females using the mean addiction score from SAS-SV. mental health conditions (Omer, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%